SM Analyzer and Persona-Based Visualization: The Concept of Systemic Avatar - Maia, Maria Beatriz dos Reis; Sa, Ruan Rolin; Sousa, Léia Sousa De; Araujo, André de; Santos, Rogério Carvalho dos; Silva, Rogério Rômulo da; Vieira, Alex de Souza; Kuribayashi, Hugo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: In the current context, digital presence has become essential for businesses, especially micro and small businesses, facing challenges in migrating to cyberspace and understanding social media data. Problem: Business owners face difficulties in interpreting graphs and understanding social media data, which are essential for strategic decision-making. Proposed Solution: The paper presents the concept of Systemic Avatar and the SM Analyzer tool, which collects real-time data from your social networks and automatically generates a unique persona representative of the set of people who follow these networks. Information Systems Theory: The research is based on Systems-of-Information Systems theory, using the concept of Systemic Avatar to offer a new perspective on the visualization and interpretation of social media data. Method: A literature review and a survey of micro and small entrepreneurs in the Amazon region of Brazil were conducted, applied with 28 affirmative questions grouped into 4 research axes. Summary of Results: The results indicate the potential adoption of the SM Analyzer tool by micro and small entrepreneurs in the Amazon region. Contributions and Impact on the Information Systems Area: The work contributes with the proposal of the concept of Systemic Avatar, the presentation of the SM Analyzer tool, and the expansion of the level of digital maturity of companies in this region, positively impacting the area of Information Systems.